2013
DOI: 10.2981/12-133
|View full text |Cite
|
Sign up to set email alerts
|

Whooping craneGrus americanachick mortality and management intervention

Abstract: Translocation of captive-reared animals is widely used as a tool for endangered species recovery. Frequently, translocated populations have relatively low initial productivity, requiring management intervention. A translocated population of whooping cranes Grus americana in central Wisconsin is such a case. We examined chick mortality for this population and used daily chick survival rates as our response variable to model several parameters including phenology, chick age, energetics and parent age and experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A separate study found 84% of wild sandhill cranes that had granulomas were also shedding oocysts in the feces [ 19 ]. Wild whooping crane chicks are associated with high mortality (27%- 68%) during the first 20 days after hatching [ 20 22 ], and the role of DVC as a cause of wild chick mortality is poorly understood [ 11 ]. Additionally, infection with these Eimeria species may make surviving birds more susceptible to other disease or predation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A separate study found 84% of wild sandhill cranes that had granulomas were also shedding oocysts in the feces [ 19 ]. Wild whooping crane chicks are associated with high mortality (27%- 68%) during the first 20 days after hatching [ 20 22 ], and the role of DVC as a cause of wild chick mortality is poorly understood [ 11 ]. Additionally, infection with these Eimeria species may make surviving birds more susceptible to other disease or predation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reintroductions and translocations, the human‐mitigated movement of organisms from one area to release in another (International Union for Conservation of Nature ), are conservation management tools that provide a unique opportunity to explore these behavioral responses. Although accounting for behavior has been recognized as an important element to successful wildlife management, many reintroduction and translocation projects have occurred without understanding or consideration for behavioral responses, potentially limiting the success of translocation efforts (Letty et al , Sheean et al ), where success may be measured by survivorship (Troy et al ), breeding success (King et al ), integration into an existing population (Scillitani et al ), or restoration of key ecological functions (Griffiths et al ). For example, a study of northern water snakes ( Nerodia sipedon sipedon ) found thermoregulatory behaviors were impaired in translocated individuals, leading to management recommendations that included matching pre‐ and post‐translocation habitat conditions, releasing individuals into enclosures, and enriching environmental conditions for captive snakes prior to translocation (Roe et al ).…”
mentioning
confidence: 99%
“…The nesting phase is the most vulnerable period for many threatened ground‐breeding birds (Assersohn et al., 2021 ). Findings indicate that half of Whooping Crane ( Grus americana ) chick mortalities occur during hatching and before the chicks are 1 month old (King et al., 2013 ), while the hatching rate of GCCs is also low (Gichuki, 2000 ). While any approach to a nest site or family grouping for monitoring purposes likely causes some level of disturbance, researchers should note the response of the parents, which may vary depending on the perceived level of danger to either themselves or their offspring (Dowling & Bonier, 2018 ; Lima, 2009 ).…”
Section: Discussionmentioning
confidence: 99%